Non-alcoholic fatty liver disease: molecular and cellular interplays of the lipid metabolism in a steatotic liver - Ramos, Leticia F. [UNESP]; Silva, Caio M. [UNESP]; Pansa, Camila C. [UNESP]; Moraes, Karen C. M. [UNESP] (Taylor & Francis Ltd, 2020)
Introduction: Non-alcoholic fatty liver disease (NAFLD) affects similar to 25% of world population and cases have increased in recent decades. These anomalies have several etiologies; however, obesity and metabolic dysfunctions are the most relevant causes. Despite being considered a public health problem, no effective therapeutic approach to treat NAFLD is available. For that, a deep understanding of metabolic routes that support hepatic diseases is needed. Areas covered: This review covers aspects of the onset of NAFLD. Thereby, biochemistry routes as well as cellular and metabolic effects of the gut microbiota in body's homeostasis and epigenetics are contextualized. Expert opinion: Recently, the development of biological sciences has generated innovative knowledge, bringing new insights and perspectives to clarify the systems biology of liver diseases. A detailed comprehension of epigenetics mechanisms will offer possibilities to develop new therapeutic and diagnostic strategies for NAFLD. Different epigenetic processes have been reported that are modulated by the environment such as gut microbiota, suggesting strong interplays between cellular behavior and pathology. Thus, a more complete description of such mechanisms in hepatic diseases will help to clarify how to control the establishment of fatty liver, and precisely describe molecular interplays that potentially control NAFLD.
Keywords: Epigenetics; gut microbiota; hepatic steatosis; metabolic pathways; non-coding RNAs; systems biology